2019
DOI: 10.14814/phy2.14089
|View full text |Cite
|
Sign up to set email alerts
|

Expression of SLC 4A11 protein in mouse and rat medulla: a candidate transporter involved in outer medullary ammonia recycling

Abstract: SLC 4A11 is a multifunctional membrane transporter involved with H + transport, NH 3 and alkaline pH stimulated H + transport, and water transport. The role of SLC 4A11 in the kidney is not well understood. A prior study has shown that in murine kidney, SLC 4A11/LacZ staining is primarily in the long‐looped descending thin limb ( DTL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“… 40 Slc4a11 is known to be expressed in DTL cells, although expression has been described only in the medullary part of the kidney. 41 …”
Section: Resultsmentioning
confidence: 99%
“… 40 Slc4a11 is known to be expressed in DTL cells, although expression has been described only in the medullary part of the kidney. 41 …”
Section: Resultsmentioning
confidence: 99%
“…Parents of CHED children who are heterozygous for SLC4A11 mutations also appear to be at risk of developing FECD [ 34 ]. No other human disorders have been definitively associated with SLC4A11; however, there are some reports from animal models that suggest kidney involvement (polyuria) [ 32 , 35 , 36 , 37 ] and submandibular gland dysfunction [ 38 ], which is consistent with the strong expression of SLC4A11 in these tissues.…”
Section: Disease Associationsmentioning
confidence: 89%
“…Whether this is due to dysfunctional autophagy or lysosome production remains to be examined. SLC4A11 is expressed in the kidney medulla [ 32 , 36 ] and the knock-out yields urine hypo-osmolarity [ 32 , 35 ]. Based on anatomical location within the outer medulla, it is conceivable that SLC4A11 has a role in countercurrent ammonia transport [ 36 ].…”
Section: Studies Of Slc4a11 In Non-cornea Tissuesmentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Gee et al 54 showed the expression of Slc4a11 in the upper descending thin limbs of the mouse kidney, which was hypothesized as a transporter-modulating ammonia recycling in the outer medulla. Slc4a11 localization to kidney mitochondria and OCR analysis using isolated kidney mitochondria reveal similar characteristics of SLC4A11 as in corneal endothelium and transfected fibroblasts.…”
Section: Discussionmentioning
confidence: 99%